Analisis Kemampuan Produksi Auksin dari Bakteri Endofit dan Plant Growth Promoting Rhizobacteria (PGPR) dalam Akar Cabai Merah Keriting (Capsicum annum L.) - Maulida, Nurdalila; Rahmawati, Arrum; Dewi, Tirta Kumala; Simarmata, Rumella; Widowati, Tiwit; Kartika, Titik; Guswenrivo, Ikhsan; Nugroho, Deddy Triyono; Supriatna, Ateng (MANILKARA: Journal of Bioscience, 2024)
Endophytic bacteria found in the roots, stems, and leaves of plants have potential as biocontrol agents and drivers of plant development, besides that in plant roots there are also plant growth promoting rhizobacteria (PGPR) with the same ability. The consortium of the two bacteria will produce Indole 3 acetic acid (IAA) compounds which are then converted into auxins that are beneficial to plants. The research aims to determine the ability of endophytic bacteria and PGPR from the roots of curly red chili plants in producing auxin hormones. The research work procedure includes rejuvenation of bacterial isolates, macroscopic and microscopic characteristics, measuring auxin levels using HPLC (High Performance Liquid Chromatography). The results showed that the consortium of 6 bacteria (3 endophytes and 3 PGPR) produced an auxin concentration of 46.122 ppm, a consortium of endophytic bacteria of 24.201 ppm, a consortium of PGPR bacteria of 162.723 ppm, and finally single endophytic bacteria and single PGPR bacteria produced auxin of A 158.913 ppm; B 64.882 ppm; C 93.923 ppm; CB1 240.817 ppm; CB2 186.807 ppm; and CMBC 11.689 ppm, while for the control 0 ppm. In conclusion, the highest auxin concentration was obtained from the single result of PGPR bacteria CB1 240.817 ppm.